A Trusted Low-Latency Multipath Routing for Mission-Critical Tactical Data Transfer - Keum, Dooho; Lim, Jihun; Ko, Young Bae (Journal of Korean Institute of Communications and Information Sciences, 2020)
In the tactical network, a reliable routing protocol is required to quickly and safely transfer huge amounts of data from various mission critical data and sensors. In particular, the military environment emphasizes the urgency, importance, confidentiality of data so the reliability and quality of the required data must be guaranteed. This requires a routing protocol that can detect nodes performing malicious attacks that discard and modify confidential data to ensure the quality of service. In this paper, we proposed a trusted low-latency routing protocol that can detect malicious nodes and satisfy the requirements of mission critical data. The proposed scheme is verified through OPNET simulator and confirmed the improved network performance result compared to the existing schemes.
Keywords: Mission critical; Quality of Service; Tactical Network; Trusted Low-Latency Multi-path routing; Trustworthiness